Factors of Preparation of HighQuality Clinker in Rotary Kilns (Eurasian Research Bulletin, 2023)
The effect of the cement clinker baking process on cement strength is studied in the article. The process of formation of clinker, which is a solid inorganic substance composed of cations and anions of various compositions combined with protons and hydroxyl groups in liquid rocks, forms the basis of the composition of cement, and quality cooking factors and the basics of economical use of gas fuel in cooking clinker raw materials.